Absorption spectroscopy and energy levels of rare earth impurity centres in SrxBa1-xNb2O6 crystals - Demirbilek, R.; Kutsenko, A. B.; Pankrath, R.; Kapphan, S. E. (WILEY-V C H VERLAG GMBH, 2009)
The absorption spectra of Ce3+, Nd3+, Eu3+, Tb3+, Er3+, Tm3+ and Yb3+ rare earth (RE) impurity ions incorporated in SrxBa1-xNb2O6 (SBN) crystals were studied in a wide spectral range from the visible to the mid-infrared. On the basis of the analysis of the Cd3+ absorption line shapes and their polarization properties the conclusion was drawn about the incorporation of multiple Ce3+ centres mostly in the position Al of the crystal lattice of SBN. From the observed temperature dependence of the Ce3+ absorption line broadening the electron coupling strength (160 cm(-1)) and effective phonon energy (300 cm(-1)) were determined. (C) 2009 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim
Keywords: STRONTIUM-BARIUM NIOBATE; PHONON COUPLING STRENGTH; LANTHANIDE-ION SERIES; DOPED SBN; SR0.61BA0.39NB2O6; LUMINESCENCE; RESONANCE; SPECTRA; BAND; CE; Physics